Structural and functional cold adaptation of AMS8 lipase through in-silico, physicochemical and biophysical approaches - Mohd Fuzi, Siti Farhanie (2017)
Psychrophilic organisms and their enzymes have increasingly attracted the attention of researchers due to their peculiar properties that allow them to remain active in cold conditions. Investigating the relationship between stability, flexibility and specific activity of such enzyme may serve as tools for biotechnological purposes. In this study, cold active lipase from psychrophilic Pseudomonas sp. strain AMS8 obtained from Antarctic soil is subjected to in-silico, physicochemical and biophysical study. The aim is to provide a better understanding on the functional and structural adaptations of cold active lipase. Employing an in-silico approach, prediction of a three dimensional structure for AMS8 lipase was done using Pseudomonas sp. MIS38 lipase (PDB ID : 2Z8X) crystal structure as template, followed by molecular dynamic simulation at various temperatures. Protein was expressed and purified to homogeneity for kinetic study, physicochemical and biophysical studies. The kinetic study was carried out to determine catalytic properties of AMS8 lipase which recorded for the value of Vmax and Km to be 0.5892 μmol/min and 9.790 10-5M respectively. Structural properties of AMS8 lipase at different temperatures were studied using circular dichroism, differential scanning calorimetry, and fluorescence monitoring to reveal about protein structure at low temperature. Circular dichroism results suggest that AMS8 lipase shows typical α/β folds which normally seen in the hydrolase group of enzymes. AMS8 lipase does not fully lose its secondary structure at high temperature. AMS8 lipase was seen to denature at 51°C and the denaturation was thermally irreversible as recorded by differential scanning calorimetry. The fluorescence study suggested that high temperatures induced transition of folded protein to unfolded protein and molten globule form of AMS8 lipase was suggested at 40°C. Secondary structure disruption occurred at higher temperatures to greatly affect the exposure of the hydrophobic surface of the protein. The crystallization attempt managed to produce reproducible crystal in diamond shape using a formulation of 0.1 M HEPES (pH 7.5), 10% w/v polyethylene glycol 8,000 and 8% v/v ethylene glycol after incubation at 15°C. In conclusion, structural adaptations of AMS8 lipase at low temperature are characterized by an improved in flexibility of the non-catalytic domain while the catalytic domain retains rigidity at low temperatures.However, both the catalytic and non-catalytic domains are greatly affected by elevated temperature higher than 30°C to cause disruption of the catalysis ability of the protein.